DRUG USE AND ALCOHOL ABUSE AMONG INMATES – CAUSES, CONSEQUENCES, PREVENTION - Andreea – Cătălina FORȚU; Cornelia RADA (Anthropological Researches and Studies)
Objectives. Drug use and alcohol abuse are initially a physical and mental health problem at the individual level, later with direct effects on public safety and security. In order to understand what are the appropriate measures in preventing and reducing these phenomena, this paper aimed to analyze the causes and consequences of substance use among inmates. Material and Methods. This literature review was developed from a survey of relevant articles published online between 2000 and 2023, identified in the Oxford Journals, Research Gate, PsychInfo, Web of Science and Google Scholar databases. A total of 91 articles were analyzed, with qualitative and/or quantitative study samples totaling 31,253 inmates. Results. In terms of identifying variables that are predictive for substance use, the individual’s risk profile captured elements such as impulsivity (8 studies), sensation seeking (7 studies), hopelessness (4 studies), low agreeableness (3 studies), introversion (3 studies), extraversion (3 studies) and high neuroticism (2 studies). The risk environment factors identified were criminal history, low social support, insufficient financial resources, presence of domestic violence and availability of drugs, alcohol in the family or entourage. Conclusions. This literature review highlighted that the drug and alcohol use among inmates is associated with increased crime rates and medical problems, including HIV and hepatitis C infections. Research has underlined the importance of specialized interventions in prisons and in the post-release period to prevent relapse to drug use. Prevention should focus on screening, specialized treatment and post-release support, involving collaboration between institutions and families.